Simulation of Tunnel Junction in Cascade Solar Cell (GaAs/Ge) Using AMPS-1D - Benmoussa Dennai; H. Ben Slimane; A. Helmaoui (Журнал нано- та електронної фізики)
The development of the tunnel junction interconnect was key the first two-terminal monolithic, multi-junction solar cell development. This paper describes simulation for the tunnel junction (GaAs) between top cell (GaAs) and bottom cell (Ge). This solar cell cascade was simulated when using one dimensional simulation program called analysis of microelectronic and photonic structures (AMPS-1D). In the simulation, the thickness of the tunnel junction layer was varied from 10 to 50 nm. By varying thickness of tunnel junction layer the simulated device performance was demonstrate in the form of current-voltage(I-V) characteristics and quantum efficiency (QE).